2022
DOI: 10.1039/d2nj00383j
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in tin ion detection using fluorometric and colorimetric chemosensors

Abstract: The innovation of chemosensors for tin ions (Sn4+/Sn2+) has evolved as a key research topic in recent decades, garnering a lot of attention due to its environmental, industrial and biological...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 113 publications
1
5
0
Order By: Relevance
“…This situation has also been demonstrated in animal studies. By comparing different intensities of swimming exercise on reproductive dysfunction in mature male albino Wistar rats, Manna et al found that prolonged high intensity training is negatively correlated with reproductive hormones and semen parameters (31). Similar results were found in another study in a rat model (32).…”
Section: Discussionsupporting
confidence: 55%
“…This situation has also been demonstrated in animal studies. By comparing different intensities of swimming exercise on reproductive dysfunction in mature male albino Wistar rats, Manna et al found that prolonged high intensity training is negatively correlated with reproductive hormones and semen parameters (31). Similar results were found in another study in a rat model (32).…”
Section: Discussionsupporting
confidence: 55%
“…However, excess accumulation of tin may seriously interfere with respiratory, digestive and nervous systems. In the environment, excess tin may result from the degradation pathway of another PBT, tributyltin chloride [6,7]. Aluminum is extensively released in the environment owing to its wide application in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36] However, fluorescence, chemiluminescence, and bioluminescence spectroscopic techniques have attracted a lot of interest from scientists because of their great sensitivity, outstanding selectivity, ease of operation, accuracy, affordability, quick response, low detection limits, non-invasive and nondestructive nature, high temporal and spatial resolution, and real-time monitoring capability in biological cells. [37][38][39][40][41] With this objective in mind, much effort has been expended over the past few decades to develop optical chemodosimeters (fluorescence, chemiluminescence, and bioluminescence) that can selectively detect O 3 . Generally, chemosensors are molecular probes that selectively and irreversibly interact with analytes (cation, anion or neutral molecules) to generate a recognizable change that can be detected with the naked eye or using some efficient techniques.…”
Section: Introductionmentioning
confidence: 99%
“…31–36 However, fluorescence, chemiluminescence, and bioluminescence spectroscopic techniques have attracted a lot of interest from scientists because of their great sensitivity, outstanding selectivity, ease of operation, accuracy, affordability, quick response, low detection limits, non-invasive and non-destructive nature, high temporal and spatial resolution, and real-time monitoring capability in biological cells. 37–41…”
Section: Introductionmentioning
confidence: 99%